Taxonomic characterization of a marine Nannochloropsis species, N. oceanica sp. nov.(Eustigmatophyceae) - Suda, S.; Atsumi, M.; Miyashita, H.
Ten strains of Nannochloropsis species in the Marine Biotechnology Institute Culture Collection (MBIC), Japan, were classified as N. granulata (one strain), N. salina (one strain), N. gaditana (three strains)and N. oceanica Suda & Miyashita sp. nov. (five strains)by determining nearly complete 18S rDNA sequences. The 18S rDNA sequences of strains belonging to the same species were all identical. Rubisco (rbcL)gene sequences of the 10 strains were also determined. The substitution frequencies among the rbcL genes in these four species were more than three times higher than those among 18S rDNA, especially between N. gaditana and N. salina, where 16 substitutions in the rbcL genes were found, in contrast to one substitution in 18S rDNA. These data suggest strongly that rbcL gene sequences provide better resolution than 18S rDNA sequences for classification of Nannochloropsis species. Morphology was characterized by light microscopy (LM)of exponentially growing cells. Cells of N. gaditana and N. salina were cylindrical to oval. The majority of cells of other species were globose. Cells of N. granulata had many refractile granules and other granular inclusions, which exhibited vigorous Brownian movement. Few N. oculata had refractile granules. Some N. oceanica had refractile granules and granular inclusions that were nonmotile. LM observation of old cells and electron microscopy of cells of all growth stages revealed no morphological traits that distinguish between these species.
Keywords: ALGAE; EUKARYOTA; EUSTIGMATOPHYCEAE; MIYASHITA; NANNOCHLOROPSIS; NANNOCHLOROPSIS GADITANA; NANNOCHLOROPSIS GADITANA